AGAMA DAN POLITIK: Mengurai Noktah Merah Politik Identitas di Indonesia - Soenjoto, Wening Purbatin Palupi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
Indonesian politics that Generation Z learns on social media becomes practical politics that are easily shaped with the preferences of politicians' characters on social media. Politicians who are supported by religiously affiliated parties are still very influential. Religious issues are a magnetic force that can be a medium for gaining votes. This study is to analyze the understanding and meaning of practical politics about Islam by Generation Z in politics in Indonesia based on Islamic religious issues. Using a qualitative research method with a phenomenological approach and conducting open interviews with 50 respondents aged 18-21 years to obtain research results that can be analyzed descriptively. Issues about religion, especially about Islam, will always influence the world of Indonesian politics. The lack of literacy about politics and Indonesian political history learned by Generation Z makes it easier for politicians to carry out social framing wrapped in Islamic-affiliated parties to facilitate vote-gaining.